A conceptual framework to determine usability criteria for family of products for older Malaysians - Zareei, Hassan; Mohd Yusuff, Rosnah; Syed Abdul Rashid, Sharifah Norazizan; Hussain, Mohd Rizal (2010)
This study proposes a conceptual framework which has three steps to derive and rank usability criteria for family of products related to Instrumental/Enhanced Activity of Daily Living (I/EADL). The three steps include, measuring level of functional disability by a modified IADL scale to obtain the kind and level of disability and identify related family of products, developing an initial list of recognized usability factors, and conducting Focus Group Discussion (FGD) process to develop and rank a complete list of usability crite-ria for family of products to support I/EADL. The proposed method can be used to evaluate product usability and create a helpful link between level of usability and IADL scale, thereby making better decision in purchasing each family of product for older Malaysians.